Strengthening GTRA Institutions in Responding to the Challenges of Agrarian Reform in Rejang Lebong Regency - Rineksi, Trisnanti Widi (Sekolah Tinggi Pertanahan Nasional, 2022)
To accomplish agrarian reform (RA) which aims to improve people's welfare by rearranging the structure of land tenure along with community empo¬wer¬ment, organizational elements with solid synergy are required. The Rejang Lebong Regency Government, BPN, the Alliance of Indigenous Peoples of the Archipelago (AMAN), and other elements of the Agrarian Reform Task Force (GTRA) supported by the Presidential Staff Office (KSP) have been trying to carry out this mandate since 2017. This paper aims to provide an overview of the implementation of RA, the challenges faced by the RA institutions in Rejang Lebong Regency. The method used is descriptive qualitative research. The collected data and information is then analyzed into several categories, namely the settlement of potential land objects for agrarian reform (TORA), agrarian conflict resolution, asset management which is followed up with com¬munity empowerment as outlined in the Kampung Reforma Agraria Project, and the role of RA institutions. The findings in this study are that the implementation of RA in Rejang Lebong Regency, which is fully supported by the commitment of the local government, initiatives from the community, and support from the ministry of vertical institutions (especially the Ministry of ATR/BPN, KLHK, and KSP), answers various challenges that arise, especially in terms of cross-sectoral coordination. However, there needs to be a more operational implementing regulation as a derivative of Perpres no. 86 of 2018 as a supporter and reinforcement of the policies issued by GTRA.